Freedom of Religion and Gender Equality in Sustainable Development Agenda - Khansadhia Afifah Wardana; Rahayu Rahayu; Sukirno Sukirno (Sriwijaya Law Review, 2022)
The implementation of Sustainable Development Goals (SDGs) often lacks in human rights perspective, although the goals themselves were created based on the human rights principles. However, further studies in development and international human rights law show that it is essential to highlight that particular relationship. As a member of the international community, states have an extraterritorial obligation to assist one another in developing and fulfilling the human rights of their people. Particularly in the field of freedom of religion or belief and gender equality, which creates a domino effect on other women's rights such as access to justice and education. Although SDG 2030 has expressed its commitment to respect, protect, and promote fundamental freedoms, including one's religion, and to achieve gender equality, the antagonistic construction between those two issues possibly harm the womenâ€™s rights movement and does not adhere to the â€œno one left behindâ€ principle. The lack of recognition between those issues would be damaging and could be deemed a failure to achieve the sustainable development goals. This research was conducted through a qualitative legal analysis by analysing relevant literary sources to understand the hidden link between freedom of religion or belief and gender equality within the sustainable development agenda. Clarity of these complex elements can be beneficial in creating a tool in advocating for womenâ€™s rights, especially for those who belong to religious and belief minorities.